Formulasi Dan Uji Evaluasi Antibakteri Masker Gel Peel-Off Ekstrak Bunga Telang (Clitoria ternatea L.) Dengan Variasi Gelling Agent PVA - Ajimahtinur, Selma; Ulfa, Ade Maria; Saputri, Gusti Ayu Rai (Peneliti.net, 2024)
Acne is a skin condition that occurs due to excess oil causing clogged pores, acne can experience inflammation caused by Staphylococcus aureus bacteria. Butterfly pea flower (Clitoria ternatea L.) has an active substance as an antibacterial. This study aims to determine the concentration of PVA gelling agent in peel off gel mask preparations of butterfly pea extract which is good at inhibiting Staphylococcus aureus bacteria and fulfilling physical evaluation. Extraction of butterfly pea flower using ultrasonic method with 96% ethanol solvent. PVA concentration used F1 10%, F2 12%, F3 14%. Physical evaluation tests included organoleptic tests, homogeneity, pH, spreadability, drying time, irritation tests and hedonic tests. Antibacterial activity test using well diffusion method. The activity results of the inhibition zone formed at 10% PVA concentration were 9.70 mm, 12% PVA concentration were 8.43 mm, and 14% PVA concentration were 7.13 mm. Antibacterial test results were analyzed using ANOVA and LSD follow-up test. The results of the statistical analysis showed that there were significant differences in the inhibition zones, namely 0.000 (sig <0.05) between all formulations. Based on the results of the study, it can be concluded that the Peel off gel mask with butterfly pea extract with the PVA gelling agent variation has the best physical properties and has the greatest inhibitory activity in formulation 1 with a PVA concentration of 10%..